The role of Auto rickshaw drivers on income performance among society in Banadir region-Mogadishu-Somalia - Mohamoud, Abdullahi (IJRDO - Journal of Applied Management Science, 2023)
In the present era, it can be said that growing population has placed a higher demand on the transport system. Due to the prevalence, three wheelers bridge the gap between public transport and door-to-door services, providing an alternative to private vehicles (Transport, 2012). The purpose of this study was to assess The role of Auto rickshaw drivers on income performance among society in Banadir region-Mogadishu-Somalia. The target population was 301 respondents while sampled 172 using Sloverns formula from different people including drivers and non-drivers. The study showed that the role of both Bajaj owner drivers and rental drivers were significantly affect to the’ overall income performance among society since p-value is less than .05 0r 5%. It was found that working hours on a day have increased, as drivers try to compensate for lost earnings on the following rest day for the percentage of 62.2%. In addition that, the study shows that Been a taxi Rickshaw rental driver has become the mainly option for those who have insufficient money to cover their lives with the percentage of 73.3%.The study recommended that the Bajaj owners reduce rent price per day to satisfy both rental drivers and customers.